Determinants of voluntary disclosure by Malaysian listed companies over time - Ho, Poh-Ling (Curtin University, 2009)
This thesis investigates the extent of voluntary disclosure within the annual reports of Malaysian listed firms over an eleven-year longitudinal timeframe. This research examines disclosure patterns and determinants of these disclosures in three critical years: 1996, 2001 and 2006, which respectively represent periods of self-regulation, reaction to the 1997 Asian currency crisis, and response to post-Enron influences.A comprehensive index comprising 85 items is used to measure the extent of voluntary disclosure. There is a statistically significant increase in the extent of voluntary disclosure over the eleven-year period. Voluntary disclosure increases from 22.97% in 1996 to 34.12% in 2006. The largest increase occurs between 1996 and 2001, a time of great internal angst brought about from the 1997 crisis. Findings also reveal that global corporate scandals and the external regulatory pressures provided stimulus for greater voluntary disclosures, albeit moderate, increase between 2001 and 2006. Voluntary disclosures for all five key sub-categories rose from 1996 to 2006 with a marked increase in the disclosure of directors and senior management and social reporting information; and moderate growth in corporate and strategic, financial and forward-looking information.Regression analysis results show that a company‟s voluntary disclosure practice is positively responsive to the strength of corporate governance structure in post-crisis and post-Enron periods. Ownership concentration and firm size have a positive and statistically significant association with the extent of voluntary disclosure throughout all the observation periods. These findings are consistent with agency theory tenets.Overall, the results from this study have wide-ranging implications for Malaysian regulators and policy-makers in: (i) encouraging the trend of disclosure to enhance transparency and accountability, and (ii) the implementation of a sound corporate governance framework to reduce information asymmetries between management and shareholders. The trend analysis of aggregate and specific voluntary disclosure provided in this thesis should allow stakeholders to better assess the firm‟s activities.